EFFECT OF GA3 AND NAA ON GROWTH AND YIELD OF CABBAGE (BRASSICA OLERACEA VAR. CAPITATA L.) CV. PRIDE OF INDIA - CHAURASIY , JAGDEEP; M. L. MEENA; H. D. SINGH; A. ADARSH; P. K. MISHRA (The Bioscan, 2014)
The experiment was conducted during rabi season 2012-13 at the Horticultural Research Farm of the Department of Applied Plant Science (Horticulture), Babasaheb Bhimrao Ambedkar University, Vidya Vihar Raebareli Road Lucknow -226025 (U.P.), India to study the response of cabbage cv. Pride of India to foliar application of PGRs namely GA3 and NAA with different concentrations. The experiment was laid out in Randomized block design with three replications and seven treatments, the treatments comprised of three levels of each PGRs namely GA3 (30, 60, 90 ppm) and NAA (40, 80, 120 ppm) along with control. Foliar spray of GA3 and NAA was given at 30 and 45 DAT of cabbage. Looking to the results, it was noticed that GA3 60ppm significantly increased the plant height (33.26 cm), number of leaves (21.48), plant spread (55.59 cm), stem diameter (3.05 cm), plant weight (2.44 kg), head weight (1.73 kg), head diameter (18.88 cm ) as well as head yield (51.26 t/ha) than the other treatments and control. Therefore it may be concluded that foliar application GA3 60 ppm or NAA 80 ppm can be recommended to cabbage growers for obtaining better growth and yield of cabbage.